PENGUATAN KARAKTER PEDULI LINGKUNGAN DENGAN MEMANFAATKAN SARANA DAN PRASARANA SEKOLAH MIN 7 TANGERANG - Zeta Hazara Samsul Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is entitled Strengthening the Character of Caring for the Environment by utilizing school facilities and infrastructure. The research was conducted at MIN 7 Tangerang using qualitative research methods. The general objective of this research is to find out how the process of strengthening character education cares for the environment by utilizing existing facilities and infrastructure in schools. The process of strengthening environmental care utilizes existing facilities and infrastructure in schools. The process of strengthening the character of caring for the environment consists of learning, exemplary, habituation, and reinforcement. By utilizing school facilities and infrastructure, students will feel happier so as to facilitate the process of strengthening the character of caring for the environment and keeping the school environment clean.